Identification and characterization of a fusarium head blight resistance gene TaACT in wheat QTL‐2DL. Issue 4 (4th November 2016) - Kage, Udaykumar; Karre, Shailesh; Kushalappa, Ajjamada C.; McCartney, Curt
Summary: Fusarium head blight (FHB) resistance in wheat is considered to be polygenic in nature. Cell wall fortification is one of the best resistance mechanisms in wheat against Fusarium graminearum which causes FHB. Metabolomics approach in our study led to the identification of a wide array of resistance‐related (RR) metabolites, among which hydroxycinnamic acid amides (HCAAs), such as coumaroylagmatine and coumaroylputrescine, were the highest fold change RR metabolites in the rachis of a resistant near‐isogenic line (NIL‐R) upon F. graminearum infection. Placement of these metabolites in the secondary metabolic pathway led to the identification of a gene encoding agmatine coumaroyl transferase, herein referred to as TaACT, as a candidate gene. Based on wheat survey sequence, TaACT was located within a FHB quantitative trait loci on chromosome 2DL (FHB QTL‐2DL) between the flanking markers WMC245 and GWM608. Phylogenetic analysis suggested that TaACT shared closest phylogenetic relationship with an ACT ortholog in barley. Sequence analysis of TaACT in resistant and susceptible NILs, with contrasting levels of resistance to FHB, led to the identification of several single nucleotide polymorphisms (SNPs) and two inversions that may be important for gene function. Further, a role for TaACT in FHB resistance was functionally validated by virus‐induced gene silencing (VIGS) in wheat NIL‐R and based on complementation studies in Arabidopsis with act mutant background. The disease severity, fungal biomass and RR metabolite analysis confirmed TaACT as an important gene in wheat FHB QTL‐2DL, conferring resistance to F. graminearum .